2001
DOI: 10.1128/iai.69.6.3569-3575.2001
|View full text |Cite
|
Sign up to set email alerts
|

Pneumolysin-Induced Complement Depletion during Experimental Pneumococcal Bacteremia

Abstract: To quantify complement depletion by pneumolysin during Streptococcus pneumoniae bacteremia, cirrhotic and control rats were infected intravenously with one of three isogenic mutant strains of S. pneumoniae expressing different forms of pneumolysin. Outcome measures included clearance of the organisms from the bloodstream, alterations in 50% serum hemolytic complement (CH 50 ) activity and complement C3 levels during infection, and serum opsonic capacity at 18 h postinfection. Cirrhotic rats had significantly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 29 publications
2
31
1
1
Order By: Relevance
“…First, vaccination with PlyD1 leads to neutralization of Ply that in turn limits damage to the lung epithelium, which allows S. pneu- moniae entry into the vasculature and initiation of bacteremia and lethal sepsis, as stated above. Neutralizing Ply could also affect the level of virulence by limiting Ply-mediated complement depletion (38), prevention of phagocytosis by autolysis (39), and reduction in polymorphonuclear cell antibacterial properties (40). However, neutralizing Ply could reduce bacteremia (37), but the observed death in our PlyD1-vaccinated mice may indicate a reduction of bacteremia without a reduction in sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…First, vaccination with PlyD1 leads to neutralization of Ply that in turn limits damage to the lung epithelium, which allows S. pneu- moniae entry into the vasculature and initiation of bacteremia and lethal sepsis, as stated above. Neutralizing Ply could also affect the level of virulence by limiting Ply-mediated complement depletion (38), prevention of phagocytosis by autolysis (39), and reduction in polymorphonuclear cell antibacterial properties (40). However, neutralizing Ply could reduce bacteremia (37), but the observed death in our PlyD1-vaccinated mice may indicate a reduction of bacteremia without a reduction in sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…PLY, one of the most extensively studied CDCs, exhibits several biological properties, such as activation of the complement system [20], platelets [21], and NLR family pyrin domain containing protein 3 (NLRP3) inflammasome [22] or stimulation of pattern recognition receptors (PRRs) [23,24]. Studies indicated that the pore-forming activity and pathogen-associated molecular pattern (PAMP) activity of the toxin form the foundation for most of the previously mentioned biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of complement for immunity to S. pneumoniae is emphasized by the identification of several mechanisms by which the bacteria can inhibit complement activity. The choline binding surface protein PspA and the capsule prevent C3b/iC3b deposition on S. pneumoniae by mechanisms that remain unclear, whereas the secreted toxin pneumolysin seems to divert classical pathway activity away from the bacteria (1,30,32,35,39,43,48).…”
mentioning
confidence: 99%